Ochratoxin A in Poultry Supply Chain: Overview of Feed Occurrence, Carry-Over, and Pathognomonic Lesions in Target Organs to Promote Food Safety - Elisabetta Bonerba; Alessio Manfredi; Michela Maria Dimuccio; Patrizio Lorusso; Annamaria Pandiscia; Valentina Terio; Angela Di Pinto; Sara Panseri; Edmondo Ceci; Giancarlo Bozzo (Toxins)
Ochratoxin A (OTA) is a mycotoxin produced by fungi species belonging to the genera Aspergillus spp. and Penicillium spp. The proliferation of OTA-producing fungal species may occur due to inadequate practices during both the pre-harvest and post-harvest stages of feed. Consequently, poultry species may be exposed to high concentrations of this mycotoxin that can be transferred to animal tissues due to its carry-over, reaching dangerous concentrations in meat and meat products. Therefore, this review aims to propose a comprehensive overview of the effects of OTA on human health, along with data from global studies on the prevalence and concentrations of this mycotoxin in avian feeds, as well as in poultry meat, edible offal, and eggs. Moreover, the review examines significant gross and histopathological lesions in the kidneys and livers of poultry linked to OTA exposure. Finally, the key methods for OTA prevention and decontamination of feed are described.